2020
DOI: 10.1111/jne.12842
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin release deficit and social cognition in craniopharyngioma patients

Abstract: Oxytocin is a neuropeptide known to affect social behaviour and cognition. Craniopharyngioma patients are considered to have an oxytocin‐release‐deficit caused by a rare tumour affecting the pituitary and/or the hypothalamus relevant for oxytocin production and release. To assess social behaviour and socio‐cognitive abilities in this patient group, we tested 13 patients and 23 healthy controls on self‐report questionnaires and an eye‐tracking paradigm including fast facial emotion recognition. Additionally, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…For example, craniopharyngeoma patients, who frequently suffer from a lesion of the HTH caused either directly by the tumor or indirectly by therapeutic resection of the tumor, were found to have a high prevalence of socio-behavioral impairments 28 , 29 . In accordance with the hypothesis that disruptions in OXT regulation may contribute to these symptoms in craniopharyngeoma patients, there have been reports of reduced OXT levels correlating with the extent of hypothalamic damage 30 along with significantly heightened levels of autistic traits and increased difficulties in rapid emotion recognition compared to controls 31 . This raises the question whether the socioemotional characteristics found in ASD could be similarly related to OXT and structural alterations in the HTH.…”
Section: Introductionmentioning
confidence: 59%
“…For example, craniopharyngeoma patients, who frequently suffer from a lesion of the HTH caused either directly by the tumor or indirectly by therapeutic resection of the tumor, were found to have a high prevalence of socio-behavioral impairments 28 , 29 . In accordance with the hypothesis that disruptions in OXT regulation may contribute to these symptoms in craniopharyngeoma patients, there have been reports of reduced OXT levels correlating with the extent of hypothalamic damage 30 along with significantly heightened levels of autistic traits and increased difficulties in rapid emotion recognition compared to controls 31 . This raises the question whether the socioemotional characteristics found in ASD could be similarly related to OXT and structural alterations in the HTH.…”
Section: Introductionmentioning
confidence: 59%
“…Patients with craniopharyngioma, one of the most common causes of hypothalamic damage, usually exhibit lower circulating levels of OT at baseline and after stimulation [ 72 ]. Several studies have been published seeking to determine whether OT deficiency was associated with changes in social cognition [ 73 ] and eating behaviors in craniopharyngioma survivors. Anecdotal cases suggested that the intranasal administration of OT improved emotional tasks and social behaviors in young survivors of craniopharyngioma with low (case report) [ 74 ] and detectable basal levels of OT (case series) [ 75 ].…”
Section: Oxytocin and Eating Behaviors: What Do We Know?mentioning
confidence: 99%
“…The search yielded 67 unique articles, of which eight studies were included. Of the eight included studies, data of 72 patients are reported on across two case reports (Cook et al, 2016;Hsu et al, 2017), one interventional study administering a single dose of 24IU intranasal oxytocin (Hoffmann et al, 2017), and five cross-sectional, case-control studies (Brandi et al, 2020;Daubenbüchel et al, 2016;Daubenbüchel et al, 2019;Gebert et al, 2018;Özyurt et al, 2020). No papers assessing genetic associations were found from the search.…”
Section: Resultsmentioning
confidence: 99%